Histologically diagnosed chorioamnionitis and neurodevelopment in premature children born before 34-week gestational age, Lima-Peru - Vila, Judith (2023)
The objective of this study was to determine the effects of histologically diagnosed chorioamnionitis on neurodevelopment of premature babies born with less than 34-week gestational age who were assessed at two-year corrected age. A secondary case-control study was carried out. Clinical data, placental histological findings, and development indexes assessed using the Bayley III scale were analyzed in 38 exposed children and 53 non-exposed children. Genitourinary infections in mothers and early sepsis were more frequent in the exposed group (p<0.005). Cognitive development, motor development and language were normal in both groups. Those children exposed to the chorionitis subtype had lower scores in the aforementioned variables. Histologically diagnosed chorioamnionitis did not show any influence on neurodevelopment in premature babies born with less than 34-week gestational age when they were assessed at two years. Longitudinal and multicenter studies are advised in order to define the long-term effects.